2022
DOI: 10.1002/pssr.202100641
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction Mechanism of β‐MnTe Thin Film with Wurtzite‐Type Structure Using Radiofrequency Magnetron Sputtering

Abstract: Manganese telluride (MnTe) compound is known to be a polymorphic chalcogenide. Recently, it has been reported that the MnTe shows nonvolatile memory properties with a significant change in resistance via a polymorphic transition between NiAs‐type (NC) structure (low resistance) and wurtzite‐type (WZ) structure (high resistance). This crystalline polymorphic MnTe is expected to realize a phase‐change memory with fast operation speed and ultralow operation energy. While the NC‐MnTe, generally designated as α‐MnT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The higher contrast in the transmittance at larger hν is attributed to the difference in the optical bandgap (E g ) between the β (2.50− 2.60 eV) and α (1.37−1.52 eV) phase. 4,33,34 This higher transmittance in β-MnTe is basically consistent with the relevant study by Han et al 35 Some discrepancies of the spectra are probably attributed to the different conditions such as substrate heating to deposit the β-MnTe film while we utilized as-deposited β-MnTe films without any heating process. The inset in Figure 1b presents the T α /T β ratio.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…The higher contrast in the transmittance at larger hν is attributed to the difference in the optical bandgap (E g ) between the β (2.50− 2.60 eV) and α (1.37−1.52 eV) phase. 4,33,34 This higher transmittance in β-MnTe is basically consistent with the relevant study by Han et al 35 Some discrepancies of the spectra are probably attributed to the different conditions such as substrate heating to deposit the β-MnTe film while we utilized as-deposited β-MnTe films without any heating process. The inset in Figure 1b presents the T α /T β ratio.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…However, due to the limitation of the experimental arrangements, it could not be measured. Moreover, the interaction coupling factor γ is calculated by the formulation described by Kim et al in eq . γ = 2 E a h ν 0 where h is the Planck’s constant and ν 0 is the optical phonon frequency. The denominator in eq is adopted from the reported value, and the γ is found to be in the range of 4–10 for the different atmosphere processed LCO_25 films, as shown in Table S2 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…MnTe, a polymorphic chalcogenide that has crystalline types with very different physical properties, is expected to be successfully applied in multilevel PCM . Researchers have found that the polycrystalline transition of MnTe can be controlled using thermal stress, and new insights have been obtained regarding the electrical conductivity mechanism of MnTe . The reversible displacement transformation between the wurtzite- and NiAs-type hexagonal structures of MnTe can be utilized to achieve PCM devices with lower power consumption and faster operation speed than those using conventional materials .…”
Section: Introductionmentioning
confidence: 99%
“…26 Researchers have found that the polycrystalline transition of MnTe can be controlled using thermal stress, 27 and new insights have been obtained regarding the electrical conductivity mechanism of MnTe. 28 The reversible displacement transformation between the wurtzite-and NiAs-type hexagonal structures of MnTe can be utilized to achieve PCM devices with lower power consumption and faster operation speed than those using conventional materials. 29 Hence, studying MnTe in detail and exploring the possibility of multilevel storage is warranted.…”
Section: Introductionmentioning
confidence: 99%